1999
DOI: 10.1177/030006059902700403
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ovum Transport in the Oviduct: The Dynamics of Oviductal Fluids in Domestic Rabbits

Abstract: Ova are captured by the oviductal fimbria and rapidly transported to the ampullary-isthmic junction of the fallopian tube. Fertilized ova and oviductal fluids are then carried medially in the fallopian tube, while undergoing maturation in preparation for entering the uterine cavity, where nidation and further development take place. This movement of oviductal fluids was visualized in a rabbit model with human chorionic gonadotropin-induced ovulation, by injection of a contrast medium into the ampulla region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, the secretion in the ampullae is more watery compared with other portions of the oviduct because of the fact that it presents a greater transudation caused by a larger epithelium surface (Jensen, 1984); thus contributing to the rapid transportation of the ovum through the oviduct during early pregnancy. The ovum usually enters the uterus 60–72 h after mating (Black and Asdell, 1958; Osada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the secretion in the ampullae is more watery compared with other portions of the oviduct because of the fact that it presents a greater transudation caused by a larger epithelium surface (Jensen, 1984); thus contributing to the rapid transportation of the ovum through the oviduct during early pregnancy. The ovum usually enters the uterus 60–72 h after mating (Black and Asdell, 1958; Osada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The fertilized ovum stays for approximately 36 h in the isthmus (days 2–3 of pregnancy) (Greenwald, 1961; Harper, 1994). It has been reported that the medial transport of the fluid towards the uterus diminishes in the isthmus (Osada et al, 1999). Interestingly, an increase in protein concentration of oviductal fluids in the rabbit on day 3 of pregnancy has been observed (Tucker and Schultz, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…On their way to the oocyte, sperm cells encounter various biological non‐Newtonian fluids, such as the cervical mucus or mucus in the epithelium of the fallopian tubes . The fluids of the female reproductive tract are characterized by high viscosities (0.1–1.4 mPa s), fluid flow, physiological temperature, and acidic pH . It was reported that spermatozoa might have different mechanisms to swim through bodily fluids.…”
Section: Creating Robotic Microswimmers With Spermatozoamentioning
confidence: 99%
“…In addition, the oviduct does undergo muscular contractions, which also contribute to ovum transport. The relative importance of these fluid dynamic mechanisms has been examined both experimentally and theoretically (e.g., Blake et al 1983;Halbert et al 1989Halbert et al , 1997Osada et al 1999;Verdugo et al 1980).…”
Section: Figurementioning
confidence: 99%
“…In addition, these muscular contractions cause undulatory movements of the ovum that may help to remove the outer cumulus mass and facilitate sperm penetration. Osada et al (1999) performed experiments to visualize fluid flow in the oviducts of rabbits. The fluid transport in the isthmic portion oscillates at one tenth of the oscillations observed in the ampulla portion.…”
Section: Figurementioning
confidence: 99%